THE RELEVANCE OF EDUCATION AKHLAQ THE MILLENIAL ERA (Study of Ibn Miskawaih's Thought) - Suyadi (STAI AN-NAJAH INDONESIA MANDIRI, 2020)
The rise of anarchism was carried out by some students in the form of brawls both between schools and between villages that occurred lately a sign of poor handling of the morals of the nation's children. If this is not immediately addressed, Moral Dedicate May occur, of course, the condition poses a serious threat to the survival of a nation's life. Ibn Miskawaih, as one of the Muslim philosophers, provided a solution to the handling of moral problems through a self-approach to God and the habit of doing good. One of his comprehensive ideas was to integrate the understanding of religion in collaboration with a philosophical understanding. There are three important themes related to the concept of morality which are often used as references by education experts, namely, something that must be met by the needs of the human body, something that must be met by the soul, something that must be met about fellow human beings. Since the beginning of modern education experts as realized the importance of psychology as an important part of fostering morality, this is in line with the concept of Ibn Miskawaih's thought that the quality of one's morality can be reached through improving the psychological and religious aspects. Through a literature study and literacy approach, this paper is intended to offer Ibn Miskawaih's concepts & ideas in instilling moral education to overcome various symptoms of a decline in moral values that flare up among millennials Keywords: Education, Ibn Miskawaih, Millennial